Larangan Memukul Gong saat Hajatan di Desa Babatan Diwek Jombang: Analisis Eksistensi dan Persepsi Masyarakat di Era Globalisasi - Sa'diyah, Khalimatus (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
Local traditions often contain inherited prohibitions that carry cultural and spiritual meanings. One such tradition in Babatan Village, Diwek Subdistrict, Jombang Regency, is the prohibition against striking the gong during ceremonial events. This study aims to explore the ongoing existence and public perception of this prohibition in the context of increasing global influence. Employing a descriptive qualitative approach, the researcher conducted observations and interviews with local residents across generations. The findings reveal that older community members still hold strongly to the belief that the gong should not be struck, associating it with ancestral respect and mystical consequences. In contrast, younger generations tend to interpret the rule more rationally, yet continue to honor it as part of cultural heritage. These results indicate that local customs have not been completely eroded by modernity, but instead are undergoing a negotiation of meaning as society evolves.